Appropriate level of cuproptosis may be involved in alleviating pulmonary fibrosis - Li, Guoxing; Peng, Lihua; Wu, Mingjun; Zhao, Yipin; Cheng, Zhe; Li, Gang (Frontiers in Immunology, 2022)
Objective Cuproptosis is a newly discovered form of programmed cell death that has not been studied in pulmonary fibrosis. The purpose of the present study was to explore the relationship between cuproptosis and pulmonary fibrosis. Methods Single-cell sequencing (scRNA-seq) data for human and mouse pulmonary fibrosis were obtained online from Gene Expression Omnibus (GEO) database. First, fibroblast lineage was identified and extracted using the Seurat toolkit. The pathway was then evaluated via Gene Set Enrichment Analyses (GSEA), while transcription factor activity was analyzed using DoRothEA. Next, fibroblast differentiation trajectory was inferred via Monocle software and changes in gene expression patterns during fibroblast activation were explored through gene dynamics analysis. The trajectory was then divided into three cell states in pseudotime order and the expression level of genes related to cuproptosis promotion in each cell state was evaluated, in addition to genes related to copper export and buffering and key genes in cellular metabolic pathways. Results In the mouse model of pulmonary fibrosis induced by bleomycin, the genes related to cuproptosis promotion, such as Fdx1, Lias, Dld, Pdha1, Pdhb, Dlat, and Lipt1, were gradually down-regulated in the process of fibroblast differentiation from resting fibroblast to myofibroblast. Consistently, the same results were obtained via analysis of scRNA-seq data for human pulmonary fibrosis. In addition, genes related to copper ion export and buffering gradually increased with the activation of fibroblasts. Metabolism reprogramming was also observed, while fibroblast activation and tricarboxylic acid(TCA) cycle and lipid metabolism were gradually down-regulated and mitochondrial metabolism was gradually up-regulated. Conclusion The present study is the first to reveal a negative correlation between cuproptosis and fibrosis, suggesting that an appropriate cuproptosis level may be involved in inhibiting fibroblast activation. This may provide a new method for the treatment of pulmonary fibrosis.